Quality of Nursing Care in Respiratory Isolation Units of Coronavirus Disease - Zahraa Hussein Ali, Waffa Abed Ali Hattab, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 has had a significant impact and challenge, especially for nursing practices, and since the quality of nursing care is one of the most important priorities in the field of health care, it has had its share of these challenges and impacts due to the epidemic. The information available about quality of nursing care in healthcare facilities during the COVID-19 pandemic is very limited. Objective: This study aimed to fill this gap by assessing quality of nursing care in respiratory isolation units of coronavirus disease. Methodology: A descriptive cross-sectional design was carried out in four hospitals at isolation units of coronavirus disease from the period (21th December, 2021 to 27th January, 2022). A non-probability (convenience) sampling method consists of (112) patient were selected convenience based on the study criteria. The tool used to measure the quality of nursing care is the Patient Satisfaction with Nursing Care Quality Questionnaire-Arabic (PSNCQQ-Ar). Results of the study: presented that patients’ satisfaction with quality of nursing care were within high score in all items because the mean more than (3.18), except for item (19) which presented that patient reflected they have low level of health (Mean = 2.8). Conclusion: The level of quality of nursing care provided to patients in the respiratory isolation units for Coronavirus disease was not affected, as the level of quality of care remained high.